2012
DOI: 10.2478/v10289-012-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Nosema spp. in Worker Bees of Different Ages During the Flow Season

Abstract: S u m m a r yThe aim of this study was to identify which Nosema species infect those Apis mellifera worker bees performing different functions in the colony. Samples were taken from different places inside and outside the hive, in the honey fl ow season. In February 2010, winter hive debris from 30 colonies was analyzed, and based on the microsporidian species identifi ed by multiplex PCR. The following bee colonies (none of which displayed clinical symptoms of the disease) were selected for further analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Duplex PCR confi rmed the presence of different microsporidia species in worker bees sampled from the same colony on different dates. The above results validate our previous observations [21] that worker bees infected with different Nosema species can inhabit the same colony [25]. Meana et al [26] also demonstrated that the origin of the sampled material plays an important role in the identifi cation of N. ceranae spores.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Duplex PCR confi rmed the presence of different microsporidia species in worker bees sampled from the same colony on different dates. The above results validate our previous observations [21] that worker bees infected with different Nosema species can inhabit the same colony [25]. Meana et al [26] also demonstrated that the origin of the sampled material plays an important role in the identifi cation of N. ceranae spores.…”
Section: Discussionsupporting
confidence: 80%
“…The effectiveness of the analyzed treatments was evaluated by the hemocytometric technique based on the number of spores, but this method was not used to identify Nosema pathogens to species level because it does not enable species identifi cation [21]. Microsporidia species were validated by duplex PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Every month from April to September 60 hive bees (HB) were sampled randomly directly from honey combs in the central part of the nest, and 60 forager bees returning to the hive with pollen (FB) were sampled from the beehive entrance using a special tool. Multiplex PCR was used to separately analyse worker bees and pollen brought by them (Sokół and Michalczyk 2012). Pollen grains from forager bees were collected using sterile tweezers.…”
Section: Methodsmentioning
confidence: 99%